Research trends in college students' sleep from 2012 to 2021: A bibliometric analysis - Zhou, Jingxin; Qu, Junchao; Ji, Siqi; Bu, Yuan; Hu, Yicheng; Sun, Huiping; Xue, Mengxin; Zhou, Ting; Qu, Jiling; Liu, Yongbing (Frontiers in Psychiatry, 2022)
Background: A great proportion of college students experience various sleep problems, which damage their health and study performance. College students’ sleep problems, which are caused by several factors, have been easily ignored before. In the past decade, more research has been published to expand our understanding of undergraduates’ sleep. The purpose of the study is to explore the research hotspots and frontiers regarding college students’ sleep using CiteSpace5.8.R3 and offer guidance for future study. Methods: We retrieved relevant literature from the Web of Science Core Collection Database and imputed the downloaded files into CiteSpace5.8.R3 for visualization analysis. We generated network maps of the collaborations between authors, countries, institutions, the cited journals, and co-occurrence keywords. The analysis of keywords clusters, timeline views, and keywords citation bursts help us identify the hotspots and research trends. Results: A total of 1841 articles related to college students’ sleep, published from 2012 to 2021, were selected. The number of publications gradually increased. Karl Peltzer was the most prolific authors with fifteen publications. The United States and Harvard University separately contributed 680 and forty articles and had the greatest impact in this field. SLEEP ranked first in the frequency of cited journals. The article published by Lund HG was the most influential publication. Based on the analysis of keywords, we summarized research hotspots as follows: current status, affecting factors, and adverse outcomes of college students’ sleep. The frontiers were the further understanding of the relationships between sleep and mental and physical health, and various interventions for sleep disorders. Conclusion: Our study illustrates the research hotspots and trends and calls for more research to expand the findings. In the future, the cooperation between institutions and authors needs to be strengthened. The complex relationships between sleep and mental and physical health and problematic substance use disorders are necessary to be explored. Longitudinal studies or randomized controlled trials should be constructed to verify the current findings or assumptions.